Genetic Aspects of Mycobacterium Tuberculosis Resistance to New Anti-Tuberculosis Drugs - A. V. Kukurika; E. I. Veselova; A. B. Peregudova (Туберкулез и болезни лёгких)
We analyzed 57 publications devoted to study of genetic mechanisms of formation of drug resistance of Mycobacterium tuberculosis to bedaquiline, delamanid, pretomanid, linezolid, and clofazimine. Identification of genetic factors of MTB drug resistance make the basis to search for new targets in development of anti-tuberculosis drugs and methods for drug susceptibility testing.